The Balance of MU-Opioid, Dopamine D2 and Adenosine A2A Heteroreceptor Complexes in the Ventral Striatal-Pallidal GABA Antireward Neurons May Have a Significant Role in Morphine and Cocaine Use Disorders - Borroto-Escuela, Dasiel O.; Wydra, Karolina; Fores-Pons, Ramon; Vasudevan, Lakshmi; Romero-Fernandez, Wilber; Frankowska, Małgorzata; Ferraro, Luca; Beggiato, Sarah; Crespo-Ramirez, Minerva; Rivera, Alicia; Rocha, Luisa L.; Perez de la Mora, Miguel; et al. (Frontiers in Pharmacology, 2021)
The widespread distribution of heteroreceptor complexes with allosteric receptor-receptor interactions in the CNS represents a novel integrative molecular mechanism in the plasma membrane of neurons and glial cells. It was proposed that they form the molecular basis for learning and short-and long-term memories. In this perspective article we discuss and propose how an increase in opioid heteroreceptor complexes, containing MOR-DOR, MOR-MOR and MOR-D2R, and their balance with each other and A2AR-D2R complexes in the striatal-pallidal enkephalin positive GABA antireward neurons, may represent markers for development of morphine use disorders. We suggest that increased formation of MOR-DOR complexes takes place in the striatal-pallidal enkephalin positive GABA antireward neurons after chronic morphine treatment in part through recruitment of MOR from the MOR-D2R complexes due to the possibility that MOR upon morphine treatment can develop a higher affinity for DOR. As a result, increased numbers of D2R monomers/homomers in these neurons become free to interact with the A2A receptors found in high densities within such neurons. Increased numbers of A2AR-D2R heterocomplexes are formed and contribute to enhanced firing of these antireward neurons due to loss of inhibitory D2R protomer signaling which finally leads to the development of morphine use disorder. Development of cocaine use disorder may instead be reduced through enkephalin induced activation of the MOR-DOR complex inhibiting the activity of the enkephalin positive GABA antireward neurons. Altogether, we propose that these altered complexes could be pharmacological target to modulate the reward and the development of substance use disorders.